2015
DOI: 10.3109/0284186x.2014.998279
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and stage at diagnosis of head and neck cancer – a nationwide study from DAHANCA

Abstract: AbstrActbackground. Socioeconomic differences in survival after head and neck squamous cell carcinoma (HNSCC) are among the greatest for any malignancy. To improve our understanding of the mechanisms by which socioeconomic position influences HNSCC survival, we investigated the association between socioeconomic position and advanced stage HNSCC at diagnosis. Material and methods. Men and women with HNSCC diagnosed between 1992 and 2008 were identified in the Danish Head and Neck Cancer Group (DAHANCA) database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 26 publications
(2 reference statements)
6
48
0
Order By: Relevance
“…Income is more likely to change during the life-course than education and therefore represents a more accurate indicator of current SEP. 23,24 Our study supports evidence from other countries such as the USA, 14 Australia 25 and Denmark 26 showing that individuals with low income are at higher risk of late-stage cancer than wealthy people. In Iran, in contrast, breast cancer patients with poor economic resources did not differ from wealthier ones in terms of tumor stage.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Income is more likely to change during the life-course than education and therefore represents a more accurate indicator of current SEP. 23,24 Our study supports evidence from other countries such as the USA, 14 Australia 25 and Denmark 26 showing that individuals with low income are at higher risk of late-stage cancer than wealthy people. In Iran, in contrast, breast cancer patients with poor economic resources did not differ from wealthier ones in terms of tumor stage.…”
Section: Discussionsupporting
confidence: 85%
“…14 In Denmark, men living alone had increased odds of advanced tumors, whereas this effect was not found in women. 26 Other studies did not find an association between cohabitation and stage. 21,22 We found that patients who lived alone had increased odds of advanced disease, adjusted for age and gender.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Because of provincial privacy standards during the study timeframe, we only had approval to access the first three characters of a patient's six‐digit postal code. This allowed reliable ascertainment of community size, but not other important census‐based information related to socioeconomic status, which have been shown to correlate with both urban–rural residence and cancer survival . A case‐control study in Ontario demonstrated that lower socioeconomic status groups had a significantly higher risk of HNC, and they were also more susceptible to a late cancer diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…The database has not only been strengthened by linkage to other registries6,7 but has also shown its value by being a supportive basis for studies of comorbidity,6 value of follow-up,14 or socioeconomical relationship in patients with head and neck cancer 15,16. In the foreseen future, it will be part of international comparisons of treatment strategies, and for such purpose, a clinical database is far superior than using cancer registry comparisons (such as the Nordic NORDCAN study), since such databases are incomplete and inaccurate regarding clinical information.…”
Section: Use Of the Databasementioning
confidence: 99%